Pengaruh Faktor Makro Ekonomi Terhadap Pembiayaan Bermasalah (Penelitian Pada Bank Umum Syariah di Indonesia Tahun 2010-2017) - Hamzah, Amir (IAIN Surakarta, 2018)
The purpose of this research was conducted to determine and test the influence of macroeconomic factors in the form of inflation, BI rate and exchange rate (kurs) toward non performing financing. Population in this research is the Islamic Banking industry in Indonesia among 2010-2016. The sampling technique used is purposive sampling where the sample is selected based on the criteria determined by the writer. The data used is secondary data sourced from the official website of each Islamic Banking. To know the influence of inflation, BI rate and exchange rate (kurs) toward non performing financing this research used eviews as statistical research tool. The research method used descriptive method with quantitative approach. This research used panel regression analyst model performance by using the four classical assumption which are normality, multicollinearity, autocorrelation and heteroscedasticity. The results show that, simultaneously Inflation, BI Rate and Exchange Rate (kurs) have significantly and positive impact on non performing financing (NPF). Then in partialy, inflation has a positive impact and not significant on non performing financing (NPF), BI rate and exchange rate (kurs) have positive and significant effect on non performing financing (NPF). Keywords: Inflation, BI Rate, Exchange Rate, Non Performing Financing (NPF) JEL Classification: C12,D81, G21a